Avaliação por CFD da fluidodinâmica e da transferência de calor em leitos de jorro para diferentes ângulos da base cônica - Souza, Amarílis Severino e (Universidade Federal de São Carlos, 2019)
The spouted bed is an equipment that provides fluid-particle contact due to the cyclic movement of solids in its interior, which results in high rates of heat and mass transfer between phases. The spouted bed is used in operations that require these features, such as drying of pastes and grains. The angle of the conical base is an important geometric factor that affects the transport phenomena in the bed. In the context of energy saving, studies involving the bed geometry may result in a more energy efficient operation. Therefore, the analysis of this parameter contributes to selection and design of spouted beds. Computational fluid dynamics (CFD) has the potential to improve the understanding of the fluid dynamic and thermal behavior of the bed. Accordingly, the objective of this work was to evaluate the influence of cone angle on the fluid dynamics and heat transfer of a spouted bed operating with sorghum particles using CFD and an Euler-Euler model. A 2D-axissimetric mesh was used. The hydrodynamic performance of each geometry was compared analyzing the solid phase circulation. The mass flow rate of the solid phase in the spout and the mean particle cycle time were used to evaluate the solids circulation rate for seven geometries with cone angles from 30° to 150° and different loads of solids. A method for obtaining the solid phase cycle time based on the Euler-Euler simulations was presented and validated. A factorial design was applied to the configurations which provided the greatest solids circulation, with evaluation of the effects of cone angle, solids load and inlet air velocity on particle circulation. The “short-circuiting” of the solid phase was evaluated using simulations in order to analyze the quality of particle circulation. The hydrodynamic model used was validated by comparison with experimental data from the literature and showed good agreement. The results of the simulations indicated that smaller cone angles and higher air inlet velocities favor the circulation of solids in spouted beds and can be used to improve the drying efficiency of sorghum in the equipment. Solids load and cone angle were the variables with the greatest effect on solids cycle time. The smaller cone angles presented higher solid flow rates in positions near the air inlet. The proposed CFD method for measurement of the particle cycle time could be applied to investigate solids circulation for other particles and spouted bed geometries. Heat transfer was simulated for the beds with cone angles of 30°, 45° and 60°, and the solid phase temperature and outlet air temperature were analyzed. A method to verify the energy balance in fluidized and spouted bed simulations was proposed. The importance of analyzing the input and output data of the simulator was discussed, emphasizing the verification of the physical consistency of the model.
Keywords: Leito de jorro; Planejamento experimental; Circulação de sólidos; Secagem; Sorgo; Fluidodinâmica computacional; Spouted bed; Factorial design; Solids circulation; Drying; Sorghum; Computational fluid dynamics; ENGENHARIAS::ENGENHARIA QUIMICA::OPERACOES INDUSTRIAIS E EQUIPAMENTOS PARA ENGENHARIA QUIMICA